Simultaneous determination of carotenoids, tocopherols, retinol and cholesterol in ovine lyophilised samples of milk, meat, and liver and in unprocessed/raw samples of fat. (15th August 2018) - Bertolín, J.R.; Joy, M.; Rufino-Moya, P.J.; Lobón, S.; Blanco, M.
Highlights: A method to analyse carotenoids and tocopherols in ovine tissues was studied. The method detected simultaneously cholesterol. Meat, milk and liver were lyophilised to reduce storage bulkiness. Raw fat samples were used because of the difficulty of lyophilisation. The method is simple, accurate and fast. Abstract: An accurate, fast, economic and simple method to determine carotenoids, tocopherols, retinol and cholesterol in lyophilised samples of ovine milk, muscle and liver and raw samples of fat, which are difficult to lyophilise, is sought. Those analytes have been studied in animal tissues to trace forage feeding and unhealthy contents. The sample treatment consisted of mild overnight saponification, liquid-liquid extraction, evaporation with vacuum evaporator and redissolution. The quantification of the different analytes was performed by the use of ultra-high performance liquid chromatography with diode-array detector for carotenoids, retinol and cholesterol and fluorescence detector for tocopherols. The retention times of the analytes were short and the resolution between analytes was very high. The limits of detection and quantification were very low. This method is suitable for all the matrices and analytes and could be adapted to other animal species with minor changes.